Treatment of functional gastrointestinal disorders in infants - O.L. Krivusha; V.L. Babich; N.Y. Leonenko (Zaslavsky O.Yu., 2019)
The article presents modern information about the main pathogenetic mechanisms and clinical manifestations of functional gastrointestinal disorders in infants according to Rome ІV criteria. The requirements for probiotic preparations used in modern medicine are presented. Attention is focused on the main characteristics of the most studied probiotic strain, Lactobacillus rhamnosus GG. The analysis of the results of clinical studies using Lactobacillus rhamnosus GG for the treatment and prevention of functional and organic diseases in children was carried out. The main pharmacological properties and characteristics of Active Flora baby food supplement are presented, which recently appeared on the pharmaceutical market of Ukraine, the main indications for the use of this food supplement are substantiated.